1994
DOI: 10.1039/c39940002007
|View full text |Cite
|
Sign up to set email alerts
|

A general route to sandwich and half-sandwich titanium imido complexes: X-ray structure of [Ti(η4-Me8taa)(NBut)](Me4taa = tetramethyldibenzotetraaza[14]annulene)

Abstract: The readily available complex [Ti(NB~t)Cl~(Butpy)~] (Butpy = 4-tert-butylpyridine) is a useful precursor to a range of sandwich-and half-sandwich titanium imido derivatives including [Ti(q-C9H4Me3) (NBut)CI(Butpy)] (C9H4Me3 = trimethylindenyl), [Ti(q-C5H5)2(NBuf)(Butpy)], [Ti(dm bpz)(NBuf)CI(Butpy)] [dmbpz = tris(3,5-dimethylpyrazolyl) borate] and [Ti(r14-Me,taa)(NBut)l { n = 4 or 8; Met4 or 8)taa = (tetra-or octa-)methyl-dibenzotetraaza[l4]annulene respectively}. Much of the current interest in transition met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 27 publications
6
46
0
Order By: Relevance
“…This can be attributed to electrostatic repulsion caused by substantial pi-electron donation from the diethylacetamidino nitrogen to the empty 3 d orbitals on Ti 4+ . The approximately linear Ti-N1-C1 bond angle (165.7 (2)°) and the short Ti-N1 bond length (1.751 (2) Å) indicate significant Ti-N1 multiple-bond character analogous to those observed in titanium(IV) imides (Guiducci et al, 2001;Lewkebandara et al, 1994;Dunn et al, 1994).…”
Section: S1 Commentmentioning
confidence: 89%
See 1 more Smart Citation
“…This can be attributed to electrostatic repulsion caused by substantial pi-electron donation from the diethylacetamidino nitrogen to the empty 3 d orbitals on Ti 4+ . The approximately linear Ti-N1-C1 bond angle (165.7 (2)°) and the short Ti-N1 bond length (1.751 (2) Å) indicate significant Ti-N1 multiple-bond character analogous to those observed in titanium(IV) imides (Guiducci et al, 2001;Lewkebandara et al, 1994;Dunn et al, 1994).…”
Section: S1 Commentmentioning
confidence: 89%
“…For the structure, see: Dunn et al (1994); Guiducci et al (2001); Lewkebandara et al (1994); Nielson et al (2001). For the reaction mechanism, see: Bradley & Ganorkar (1968); Chandra et al (1970); Forsberg et al (1987); Maresca et al (1986); Rouschias & Wilkinson (1968).…”
Section: Related Literaturementioning
confidence: 99%
“…The use of excess H 2 NtBu promotes dehydrohalogenation to form the Ti À NHtBu linkage and the ammonium salt [H 3 NtBu][Cl], while the donor ligands (e.g, pyridine, phosphine oxides) likely play several roles such as displacement of the metal-bound amine, a-hydrogen deprotonation, and formation of the titanium imide monomer. Winters seminal work has demonstrated that the presence of a Lewis base such as O=PPh 3 is critical in these reactions, since it prevented formation of the amide-amine oligomers [{TiCl 2 - [36] Mountford [5,[65][66][67] also applied an analogous strategy, generating the terminal imide group by using other donors such as pyridine, monoamines, N,N,N',N'-tetramethyl-ethylenediamine (TMEDA), among many others. Such an approach is practical given the availability of the starting materials, TiCl 4 and H 2 NtBu, and the ability to produce the corresponding titanium tert-butyl imide in multigram quantities for subsequent reactions.…”
Section: Dehydrohalogenation Deprotonation and A-hydrogen Abstractimentioning
confidence: 99%
“…Winter's seminal work has demonstrated that the presence of a Lewis base such as OPPh 3 is critical in these reactions, since it prevented formation of the amide–amine oligomers [{TiCl 2 (NH t Bu) 2 (NH 2 t Bu) 0–2 } n ] 36. Mountford5, 6567 also applied an analogous strategy, generating the terminal imide group by using other donors such as pyridine, monoamines, N , N , N ′, N ′‐tetramethyl‐ethylenediamine (TMEDA), among many others. Such an approach is practical given the availability of the starting materials, TiCl 4 and H 2 N t Bu, and the ability to produce the corresponding titanium tert ‐butyl imide in multigram quantities for subsequent reactions.…”
Section: Dehydrohalogenation Deprotonation and α‐Hydrogen Abstractimentioning
confidence: 99%
“…The chemistry of macrocyclic complexes has received much attention in recent years on account of its various applications in bioinorganic chemistry [2,3]. Transition metal complexes with macrocyclic ligands are well known for their enhanced kinetic and thermodynamic stability [4][5][6][7][8][9][10][11][12][13][14]. Many tetradentate Schiff bases are known to stabilize unusual oxidation states of the coordinated metal [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%